Molecularly Imprinted Solid Phase Extraction Aiding the Analysis of Disease Biomarkers - Silva, Matheus Siqueira (2021)
Low concentrations of biomarkers as well as the complexity of biological samples make the clinical diagnoses of several diseases a challenging task. Sample preparation protocols remain a fundamental piece in the puzzle of analytical processes, and smart sorbents including molecularly imprinted polymers (MIPs) have been successfully used in this case. In this review, we depict the state of art for the rational design of MIPs to be used in solid phase extraction of disease biomarkers from biological samples. The topics are divided into (1) strategies for MIP syntheses, (2) setups for sample preparation protocols with MIPs, (3) the applications of these combined principles in the analyses of different classes of disease biomarkers, and (4) remaining challenges and future trends for the application of Molecular Imprinting Technology in sample preparation for clinical diagnosis.